Discovery of New 3-(Benzo[b]Thiophen-2-yl)Pyrrolidine-2,5-Dione Derivatives as Potent Antiseizure and Antinociceptive Agents-In Vitro and In Vivo Evaluation - Anna Rapacz; Marcin Jakubiec; Michał Abram; Jakub Jasiński; Karolina Chrzan; Małgorzata Góra; Anna Dziubina; Katarzyna Wójcik-Pszczoła; Paulina Koczurkiewicz-Adamczyk; Katarzyna Ciepiela; Elżbieta Pękala; Jolanta Obniska; et al. (MDPI AG, 2024)
Background/Objectives: To address the unmet clinical needs in the treatment of epilepsy and pain, the continued development of more effective and safer anticonvulsants and analgesics is still necessary. Therefore, herein we report synthesis and antiseizure/antinociceptive evaluation of a focused series of 3-(benzo[b]thiophen-2-yl)pyrrolidine-2,5-dione derivatives. Methods: The anticonvulsant properties were investigated in acute models of seizures, namely the maximal electroshock (MES), the 6 Hz (32 mA), and subcutaneous pentylenetetrazole (scPTZ) seizure models, whereas analgesic activity was tested in the model of a tonic pain/formalin test and oxaliplatin-induced neuropathic pain (in CD-1-mice, i.p.). In addition, a number of in vitro assays were performed, aiming at the evaluation of the drug-like properties of the compounds disclosed herein. Results: We identified 33 as a lead compound with the most promising antiseizure properties, i.e., ED50 (MES) = 27.4 mg/kg and ED50 (6 Hz, 32 mA) = 30.8 mg/kg. Furthermore, 33 at a dose of 100 mg/kg significantly prolonged the latency time to the first seizure episode in the scPTZ model and at high doses did not impaire coordination of mice in the rotarod test (TD50 > 200 mg/kg). Apart from broad antiseizure protection, 33 demonstrated a significant analgesic effect in the formalin test (45 mg/kg, i.p.), and effectively alleviated allodynia in the oxaliplatin-induced neuropathic pain model (30 and 45 mg/kg). The binding assays suggest that the most plausible mechanism of action relies on interaction with the neuronal voltage-sensitive sodium channel (site 2). Furthermore, the drug-like potential of 33 supports favorable in vitro results, i.e., no hepatocytotoxicity and neurocytotoxicity at a high concentration of 100 μM, as well as a lack of mutagenicity at a concentration as high as 500 μM. Conclusions: Compound 33 identified in the current studies is proposed to be an interesting candidate for further preclinical development as therapy for epilepsy and neuropathic pain.